How to produce a diagnostic opinion at a distance? New forms of tele-expertise use in France and their transformational effects on healthcare practices in dermatology - Trupia, Dilara Vanessa; Mathieu-Fritz, Alexandre; Duong, Tu Anh (Frontiers in Communication, 2023)
How to produce a diagnostic opinion at a distance, without seeing and examining patients? This is the challenge of tele-expertise (TLX), defined first in legal terms, as one of the five telemedicine acts in France. It consists of a particular form of healthcare practice in which a physician, known as the "requester", solicits remotely the opinion of another practitioner, a specialist known as the "requested", by sharing with him/her clinical information and photographs that he/she produces for this purpose, based on the medical examination of the patient. This practice is certainly not new; it is inherent to any medical activity where it develops outside of any legislative and regulatory framework, between practitioners who already know each other more or less well. The novelty of the recent forms of TLX as a legally recognized medical act in its own right, relies mainly on the development of secure file exchange platforms within territorialized care networks, the systematization of these practices beyond the networks of acquaintances and their coverage by the health insurance. The purpose of this article is to describe the various usages of this new form of TLX, as well as to understand how they contribute to the in-depth transformation of care practices and organizations. It suggests doing so in the specific case of dermatology, through a qualitative study based on semi-directive interviews approximately with fifty French dermatologists, mainly requested experts, practicing TLX both in the context of private practice and in a hospital setting. The results of this empirical study are presented in three parts. First, we will consider the specificity of dermatological practice and describe the particular ways in which TLX is being implemented in this field, as a new framework. Then, we will report on the multiples efforts and skills needed to produce a diagnostic opinion remotely. We will lastly present various uses that dermatologists develop of TLX in different socio-organizational configurations. We will finally discuss how these uses transform the usual practices of dermatologists, not only by creating a new type of activity, but also by allowing them to participate differently in the organization of care pathways.